Bulk geochemical, biomarker and leaf wax isotope records of Mfabeni peatland, KwaZulu Natal, South Africa since the late Pleistocene - Baker, Andrea (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.